Effect of Hydrochloric Acid Concentration and Immersion Duration on Porous Paper Formation (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Paper, consisting of intertwining cellulose fibers, possesses a porous nature that allows liquids to penetrate and stay within its structure. This natural porosity is vital for paper's ability to absorb substances, forming the foundation of porous paper. Porous paper, which has many interconnected void spaces, is essential for breathability, filtration, and absorption in various industries, including printing, biomedical applications, sensors, and filtration. This study explores the effects of varying concentrations of hydrochloric acid (HCl) and immersion times on the fabrication of porous paper, aiming to identify optimal conditions for achieving desired porosity levels. The experimental setup involved immersing paper samples in HCl solutions with concentrations ranging from 0.1 to 0.5 M, with immersion times ranging from 30 to 180 seconds for each concentration level. The paper samples were then assessed for surface characteristics, porosity, and absorption capabilities. The results demonstrate that higher concentrations of HCl and longer immersion times generally cause the paper’s porosity to increase. However, it is noted that excessive acid concentration or prolonged immersion can compromise paper structure. The study identifies specific HCl concentrations and immersion times that optimize porosity while maintaining structural strength, which is critical for applications requiring controlled release, absorption, and filtration.
Keywords: concentration; hydrochloride acid; immersion time; porous paper